Hermann Cohen on the role of history in critical philosophy. (4th April 2021) - Edgar, Scott
Abstract: Consider two features of Hermann Cohen's critical philosophy. First, using what Cohen calls the transcendental method, critical philosophy aims to identify formal conditions of experience that are universally, and so timelessly, valid. Second, detailed, context‐sensitive surveys of the history of science and philosophy are ubiquitous in his accounts of those formal conditions. This paper argues for two claims about how those two features of Cohen's philosophy fit together. First, Cohen holds the striking view that, while philosophy aims to discover and investigate principles that are timelessly valid, it must nevertheless use historical investigation to do so. Second, Cohen has the resources to explain why, on his view, history must play this role in philosophy. This paper uses a genealogical strategy to locate that explanation in Cohen's writings: it traces views of history held by various of Cohen's teachers and shows that Cohen combines and develops those ideas to produce just the explanation needed. Ultimately, the underlying reasoning of Cohen's explanation is this. The history of science has a teleological structure, and as it unfolds, knowledge becomes increasingly universal. But then, elements of scientific theories that remain stable across a succession of increasingly universal theories will be plausible candidates for or approximations of the strictly universal formal conditions of experience. The critical philosopher is thus required to attend to the history of science to identify plausible candidates for those formal conditions.